Writing for Decision Makers / Memos and Reports with a Competitive Edge - Holcombe Marya W; Stein Judith K (Lifetime Learning Publications, 1981)
Preface, The Managerial Approach to Writing, Right Reader and Right Information, Getting the Right Answer, Structuring Your Writing, Picturing Your Strategy, Beginnings and Endings: What and Why and How, Writing the First Draft, Design for Emphasis, Revising is Quality Control, Helping Others Write Effectively, Appendixes, Ackowledgements.
Preface, The Managerial Approach to Writing, Right Reader and Right Information, Getting the Right Answer, Structuring Your Writing, Picturing Your Strategy, Beginnings and Endings: What and Why and How, Writing the First Draft, Design for Emphasis, Revising is Quality Control, Helping Others Write Effectively, Appendixes, Ackowledgements.